2007
DOI: 10.1021/bi700707u
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Role of Asp-120 in Metallo-β-lactamases,

Abstract: Metallo-beta-lactamases (mbetals) are zinc-dependent enzymes that hydrolyze a wide range of beta-lactam antibiotics. The mbetal active site features an invariant Asp-120 that ligates one of the two metal ions (Zn2) and a metal-bridging water/hydroxide (Wat1). Previous studies show that substitutions at Asp-120 dramatically affect mbetal activity, but no consensus exists as to its role in beta-lactam turnover. Here we present crystal structures of the Asn and Cys mutants of Asp-120 of the L1 mbetal from Stenotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…The value of the stereochemical parameter (37), which could discriminate between a square pyramid ( ϭ 0) and trigonal bipyramid ( ϭ 1), is 0.37 { ϭ (34). It must be pointed out that one of the carboxylate oxygen atoms of D120[76] is also involved in hydrogen bonding to the bridging hydroxide oxygen atom (Wat1), suggesting that D120[76] may be particularly important not only in orientating an OH Ϫ acting as a nucleophile to the carbonyl carbon on the ␤-lactam ring but also in positioning the Zn2 and H263 [215], as seen also in the subclass B1 and B3 MBLs (38)(39)(40). These results suggested that SMB-1 has the ability to keep the coordination geometry closer to the transition state through distortion of the regular geometry.…”
Section: Resultsmentioning
confidence: 99%
“…The value of the stereochemical parameter (37), which could discriminate between a square pyramid ( ϭ 0) and trigonal bipyramid ( ϭ 1), is 0.37 { ϭ (34). It must be pointed out that one of the carboxylate oxygen atoms of D120[76] is also involved in hydrogen bonding to the bridging hydroxide oxygen atom (Wat1), suggesting that D120[76] may be particularly important not only in orientating an OH Ϫ acting as a nucleophile to the carbonyl carbon on the ␤-lactam ring but also in positioning the Zn2 and H263 [215], as seen also in the subclass B1 and B3 MBLs (38)(39)(40). These results suggested that SMB-1 has the ability to keep the coordination geometry closer to the transition state through distortion of the regular geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures for three other MBLs of subclass B3 are available (14,15,23,53). A comparison of the structure of AIM-1 with those previously determined structures is shown in Fig.…”
Section: Table 2 Refinement Statistics For Crystal Structures Refinemmentioning
confidence: 98%
“…The resulting negatively charged tetrahedral intermediate is then stabilized by interactions with the metal, and Asp120 donates a proton to the nitrogen atom in the substrate, resulting in open-ing of the ␤-lactam ring (17). Several mutants of Asp120 in the class B3 MBL enzyme L1 from Stenotrophomonas maltophilia showed a 10-to 1,000-fold decrease in k cat compared to wild-type L1, and thus, Asp120 was confirmed to play a significant role in the hydrolysis reaction (22,23). This has also been shown for IMP-1 (24), CphA (25), and BcII (26).…”
mentioning
confidence: 96%